2022
DOI: 10.1186/s12964-022-01021-z
|View full text |Cite
|
Sign up to set email alerts
|

Wee1 promotes cell proliferation and imatinib resistance in chronic myeloid leukemia via regulating DNA damage repair dependent on ATM-γH2AX-MDC1

Abstract: Background The treatment of chronic myeloid leukemia (CML) is facing the dilemma of tyrosine kinase inhibitors (TKIs) resistance and disease recurrence. The dysfunctional DNA damage repair mechanism plays an essential role not only in the initiation and progression of hematological malignancies but also links to the development of TKI resistance. Deciphering the abnormally regulated DNA damage repair and proteins involved brings new insights into the therapy of leukemias. As a G2/M phase checkp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The phosphorylation of H2A.X, commonly known as γH2A.X, is widely detected in cells undergoing diverse modes of senescence. It is an important sign of DDR activation and necessary for the formation of repair complexes at DSBs 83–85 . Members of the phosphatidylinositol 3‐kinase‐related kinase family (PI3KK), such as ATM–Chk2 and ATR–Chk1 kinases, frequently phosphorylate H2A.X, but may not be the only ones to do so 86 .…”
Section: Morphological Features Of Senescence and Their Role In Tumor...mentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation of H2A.X, commonly known as γH2A.X, is widely detected in cells undergoing diverse modes of senescence. It is an important sign of DDR activation and necessary for the formation of repair complexes at DSBs 83–85 . Members of the phosphatidylinositol 3‐kinase‐related kinase family (PI3KK), such as ATM–Chk2 and ATR–Chk1 kinases, frequently phosphorylate H2A.X, but may not be the only ones to do so 86 .…”
Section: Morphological Features Of Senescence and Their Role In Tumor...mentioning
confidence: 99%
“…It is an important sign of DDR activation and necessary for the formation of repair complexes at DSBs. 83 , 84 , 85 Members of the phosphatidylinositol 3‐kinase‐related kinase family (PI3KK), such as ATM–Chk2 and ATR–Chk1 kinases, frequently phosphorylate H2A.X, but may not be the only ones to do so. 86 ATM is generally activated by the binding of the MRE11–RAD50–NBS1 complex to DNA breaks.…”
Section: Morphological Features Of Senescence and Their Role In Tumor...mentioning
confidence: 99%
“…It has also been reported that WEE1 can directly regulate Mus81-Eme1 endonuclease activity at stalled replication forks to prevent formation of DSBs (26)(27)(28). As a crucial component of the G2/M checkpoint, WEE1 prevents cells from entering mitosis in response to cellular DNA damage through inhibitory phosphorylation of CDK1 (27,29). In normal cells, DNA damage activates cell cycle checkpoints that arrest cells at G1 and G2 phase to repair DNA, however G1/S checkpoint defects often exist in cancer cells, preventing adequate repair.…”
Section: Introductionmentioning
confidence: 99%
“…This inhibits the autophosphorylation of BCR-ABL, prevents its activation and blocks its downstream signaling (5). However, IM drug resistance and intolerance remain an issue in certain individuals, contributing to recurrence after treatment discontinuation (6). The N-Myc downstream-regulated gene (NDRG) family, which has four members, is functionally involved in multiple biological behaviors and can be used as a biomarker for various types of diseases, including prostate cancer, nervous system diseases and liver damage (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%